Influência dos métodos de síntese na microestrutura e nas características elétricas do cátodo compósito de SrCoO3-δ– Ce0,9Gd0,1O2-δ para células a combustível de óxido sólido - Almeida, Thaís de Oliveira (2019)
The fossile fuels consumption and its emissions have been causing a great inbalance on the environment, prompting the search for forms of alternative and renewable energy. Therefore, the fuel cells, as electrochemical devices that transform chemical energy from certain fuels to electrical energy by redox reactions, are being disseminated as an alternative and renewable source. The Solid Oxide Fuel Cells (SOFC), with the possibility of being fed with ethanol, are presented with relevance to Brazil, even if their application is limited thanks to their high working temperatures. Therefore, research is nedded to make this fuel cell type usabel in large scale. In this work, a cathodic material for SOFC, the strontium cobaltite (SrCoO3-δ), was synthesized by the methods of copreciptation, combustion with urea, Pechini and gelatin. The synthesized powders were calcined at 1.000 °C for 4 hours and characterized by X-Ray Driffraction (XRD) and Scanning Electron Microscopy (SEM). The synthesized powders were mechanically mixed with gadolinium-doped ceria (Ce0.9Gd0.1O2-δ – GDC) to produce the composite samples. The films were deposited on GDC substrates by the screen-printing method and, after, were sintered at 1.100 °C for 6 hours. Lastly, the cathodic films were characterized by Impedance Spectroscopy. With the chosen synthesis methods, it was verified their influence on microstructure and electrical characteristics. The synthesis method that produced the material with monophasic perovskite structure and lowest area specific resistance (ASR), of 0.0543 Ω·cm2, at 800 °C in air, was the Pechini method.